Rotinas Do Cárcere: Uma História Social Da Casa De Detenção Da Corte Entre 1856 E 1889 - Lazarim, Anita De Souza [UNIFESP] (2017)
This research has as main objective to understand some aspects about the operation of the “Casa de Detenção da Corte” of Rio de Janeiro during the Empire. We sought to unravel the practices that existed there, how the authorities of the Ministry of Justice and the police acted and who were the prisoners and how the Casa de Detenção is mentioned at different times by the press of the time. From the analysis of the “livros de matrículas” (logbooks), we tried to find out who the prisoners were. Along with the reports of the authorities, we were able to understand better the institutional dynamics, and through the newspapers we tried to find out what was going on in the society . The research seeks to contribute to the social history of prisons, bringing a reflection on one of the parts of the main prison complex of the largest brazilian Empire city, which, however, did not have its functioning studied before. The “Casa de Correção da Corte”, the prison considered as "model", was better studied, but can we understand the prison system in the Court, and by extension, in the Empire, without understanding the other part, the Casa de Detenção itself? Little is known about the relationship between the two wings of the prison complex, this relationship can only be clarified when the Casa de Detenção operation is scrutinized. It was by detecting this gap in the History of Prisons that we proposed this Master's Degree research.